Evaluation Of The Application Of The Supervisory Results System (SRS) In The Optimization Of Supervision At The Jombang Regency Inspectorat - Fitriani, Dian; Mustofa, Amirul; Albab, Ulul (Socious Journal, 2025)
Guided by Presidential Instruction Number 3 of 2003 concerning National Policies and Strategies for E-Government Development, in 2018 the Jombang Regency Inspectorate launched the Supervisory Results System (SRS) application. SRS is an information technology-based system designed to facilitate the integrated recording, reporting, and monitoring of follow-up monitoring results, so as to speed up the data-based decision-making process that is more accurate and transparent. This application is used to improve the effectiveness and efficiency of supervision of various aspects of operations, compliance, and internal control. The purpose of this study is to evaluate the implementation of SRS applications in optimizing supervision at the Jombang Regency Inspectorate and identify the factors that cause the ineffective implementation of SRS and describe the efforts that have been made to overcome it. The research method uses a qualitative descriptive approach. Data collection techniques were carried out by interviews, observations, and documentation studies related to the implementation of SRS. The resource persons from this study are auditors and PPUPD. The results show that the use of SRS applications has had a positive impact on increasing transparency, accuracy, and speed of reporting supervision results. The SRS application is designed as a tool to increase the effectiveness and efficiency of the supervision process on the performance of local governments. The factors that cause the ineffective implementation of SRS are the limitation of human resources in mastering technology, managers are only good in terms of operations, while in terms of software development, obstacles in handling/security of cyber attacks, network management still cannot be done independently. The SRS application is still intranet-based so auditees cannot access anywhere and anytime. Therefore, it is necessary to increase the capacity of human resources by conducting digital training and strengthening infrastructure to support the implementation of applications more effectively. This research is expected to provide recommendations for the Jombang Regency Inspectorate in optimizing the use of SRS applications to improve the quality of supervision.